Analysis Business Feasibility of Saraba Traditional Beverage In Gorontalo Province - Amelia Murtisari; Isra Blongkod; Zubair Hippy (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This study aims to analyze the feasibility of saraba beverage businesses financially and non-financially in Gorontalo Province. Methodology: The study employed a quantitative descriptive approach through surveys using structured questionnaires. Samples were purposively selected, involving 16 saraba vendors and 30 consumers. Results: The analysis indicates that saraba beverage businesses are financially feasible with 12.5% R/C ratio > 1, 50% R/C ratio > 2, and 37.5% R/C ratio > 1. Finding: Non-financial feasibility is supported by a strong market potential with suggestions for flavor innovations, parking facilities, and educational promotions. Novelty: This study highlights the feasibility of saraba businesses through holistic financial and non-financial analyses, emphasizing sustainability and market development. Originality: The study provides strategic insights for saraba entrepreneurs to enhance local competitiveness. Conclusions: Saraba beverage businesses are feasible to develop, focusing on product innovation, consumer facilities, and promotions.Type of Paper: Empirical Research Article